High Step-Up ZVT Converter Based on Active Switched Coupled Inductors - Yu Tang; Haisheng Tong; Raheel Afzal; Yingjun Guo (IEEE Access)
To meet the requirements of high voltage boosting and high efficiency, a novel high step-up zero voltage transition (ZVT) DC/DC converter based on active switched-inductor (ASL) is proposed. This converter combines ASL and coupled inductor structure, thus can reduce the voltage and current stress of power switch, and the active clamping technology provides zero voltage transition (ZVT) for all switches. The coupled inductors can realize relatively high voltage gain with appropriate turns ratio while all magnetic components can be integrated in one core. In addition, thanks to the leakage inductance, the reverse recovery problem of diodes is resolved. The working principle of the proposed converter is analyzed in detail, also the characteristics including voltage gain, the condition of ZVT is discussed. Then, a family of derived converters are listed and compared to each other. According to the proposed converter, a 500W prototype with 100kHz switching frequency is established in the lab, and the experimental results are given to verify the analysis.